DETERMINAN EKSPOR MINYAK KELAPA SAWIT (CPO) PENDEKATAN ECM STUDI KASUS TAHUN 1988-2022 - Mega, Mega Shafira Permatasari; Didi Nuryadin (Develop, 2024)
The purpose of this research is to determine the factors influencing the colume of Indonesian palm oil (CPO) exports to India and to analyze the relationship between the total production of Indonesian pal oil, international palm oil prices, India’s per capita GDP and India’s foreign exchange reserves with the volume of Indonesiapalm oil exports to India. The data used in this research are secondary data obtained from Direktorat Jenderal Perkebunan, the World Bank and UN Trade. The data in this research are tested using Error Correction Model (ECM) analysis. The results of this research indicate that in the long term, India’s per capita GDP and India’s foreign exchange reserves have a positive and significant impact on the volume of Indonesian palm oil and international palm oil prices do not affect the volume of Indonesian palm oil exports to India. In the short term, variable of India’s foreign exchange reserves has a positives and significant impact, while the variables of total production of palm oil, international plam oil prce and GDP per capita do not affect the volume of palm oil exports.